The Influence of Genome Composition and Temperature on the Hatching Success and Development of the Offspring of Allotriploid Cobitis (Pisces: Cobitidae) Females - Duda, Sara; Jablonska, Olga; Boroń, Alicja; Kujawa, Roman; Janko, Karel; Juchno, Dorota (International journal of molecular sciences, 2025)
Hybridization and polyploidization are key evolutionary forces shaping fish biodiversity. But their interaction with environmental factors, such as temperature, remains poorly understood. This study examined how maternal genome composition and incubation water temperature influence the hatching success, ploidy structure, morphology and early growth of polyploid Cobitis larvae. Crosses were performed using triploid Cobitis females with three genomic compositions (EEN, EET and ETN), representing combinations of genomes from C. elongatoides (E), C. taenia (T) and C. tanaitica (N), and diploid C. taenia males as sperm donors. Fertilized eggs were incubated at 18 °C, 22 °C and 28 °C. Triploid and tetraploid offspring occurred in comparable proportions on average across all groups, but developmental abnormalities were significantly more observed in tetraploid larvae. Females with EET and ETN genomes achieved higher hatching success than those with the EEN genome. Temperature had a pronounced effect on developmental timing and success: hatching occurred earliest at 28 °C, but survival decreased and abnormalities were most frequent. These results highlight genome- and temperature-dependent trade-offs in early development of Cobitis hybrids, providing new insight into reproductive dynamics and the potential resilience of polyploid systems under climate warming.
Keywords: larva; teplota; Triploidy; ženské pohlaví; larvae development; Temperature; body length; Cypriniformes; genomic identification; Larva; hybridization; loaches; Animals; máloostní; Polyploidy; polyploidie; Genome; zvířata; mužské pohlaví; Male; larvae abnormalities; triploidie; polyploidization; genom; Female